CULTIVATING COMPASSION AT THE SCHOOL TO FIGHT OUT DISCRIMINATION PRACTICES - Marino, Samou Kamdem (PEOPLE: International Journal of Social Sciences, 2020)
Using interview sequences from collected data in the context of qualitative biographical studies of health practitioners - originating from Sub-Saharan- Africa and working in some European countries, this study focuses on the development/cultivation of Compassion, even in really difficult situations in the interaction with our fellow human beings in a globalized world. Facing rejection because of discrimination – e.g. the color of their skin, can be perceived by many persons as an offense and lead to victims automatically developing defensive behavior, which can most of the time only aggravate the already bad situation. How can using compassion help in those situations and what can educational settings contribute to cultivating compassion in the classrooms for better interpersonal relationships worldwide? Compassionate Education aims to prepare learners and instructors for cohabiting in a multicultural society, where differences are accepted and appreciated. It is thus crucial that political authorities, authors, teachers, and learners be directly involved in this global and vital issue.